A novel trust-based security and privacy model for Internet of Vehicles using encryption and steganography - Rathore, Manjari Singh; Poongodi, M.; Saurabh, Praneet; Lilhore, Umesh Kumar; Bourouis, Sami; Alhakami, Wajdi; Osamor, Jude; Hamdi, Mounir (Computers & electrical engineering, 2022)
•This research emphasizes enhancing data security in real-time IoV communication considering secure communication also presents a trust-driven privacy method using encryption and steganography for IoV, "Efficient Algorithm for Secure Transmission (EAST)," integrating encryption and steganography algorithms.•We develop a data encryption method for IoV communication and verification using distinct symmetric encryption for all three components of vehicle communication.•Development of the standards on multiple systems for secure data transmission in IoV. Comprehensive performance measurement from various angles, including transaction cost, memory overhead, processing time, and energy use.•The proposed EAST method is compared with existing AES [12], DES [13], G-DES [14], and standard LSB [15] using different indicators such as time efficiency, avalanche effect, PSNR, and file cover size. High-speed wireless network technologies play a vital role in autonomous vehicle communication systems (AVS), i.e., IoV (Internet of Vehicles), and enhance the effectiveness and reliability of the communication network. Since the size of IoV communication is rapidly growing, it is now an essential part of our regular routines. Due to its dynamic nature and massive size, it is essential to avoid any miss-communication and protect the data privacy of each vehicle.IoVallowsAVS to link remotely to each other and to various platforms and groups that may be using the same communications system. This quality link between vehicles and the need for information exchanges among vehicles introduces vulnerability and threats that can be exploited by cybercriminals. This research emphasizes on enhancing data security in real-time IoV communication. It presents a trust-driven privacy method using encryption and steganography for IoV. This method uses an Efficient Algorithm for Secure Transmission (EAST) that integrates encryption and steganography algorithms. The proposed EAST is then compared to the various current state of arts, i.e., AES (Advanced Encryption Standard), DES (Data Encryption Standard), G-DES (Generalized DES), and Standard LSB on the basis of various performance measuring parameters, i.e., encryption and decryption time, efficiency, avalanche effect, PSNR, and file cover size. Experimental results are promising for the proposed EAST method, which reported a better time efficiency of 0.86 ms, avalanche effect of 58.81%, and PSNR of 78.58%, compared to the current state arts. [Display omitted]